Georg Trakl (1887–1914) in context: poetry and experience in the cultural debates of the Brenner circle - Morgan, B (Taylor and Francis, 2013)
This article reads Trakl’s poetry in the context of his involvement with the journal ‘Der Brenner’. In particular the admiration for Karl Kraus which Trakl shared with the Brenner Circle is used as a way of showing how Trakl’s poetic method compares to the approaches of his cultural peers. The reading of Trakl that emerges lies between that of a critique of Kraus (Stieg) and a staging of literary fragmentation (Baßler). We see instead a meaningful meaningnessless that critics from the 1910s onwards, including Heidegger, have explained by grounding it in the authenticity of the poet. This strategy is read as a version of Aristotelian ēthos.